Analysis of Liquidity in Islamic Banks in Indonesia: Analysis of Capital Adequacy Ratio, Return on Asset, Inflation, and BI Interest Rate Factors for the Period 2015-2020 - Shoffan Maulana; M. Fikri Himmawan; Sri Yayu Ninglasari (IAIN Langsa, 2023)
Purpose – This study aims to explore the elements that affect the liquidity of Islamic banking in Indonesia. From 2015 to 2020, Bank Indonesia published consecutive monthly statistics that can be used in this study. Internal factors, such as the capital adequacy ratio (CAR) and return on assets (ROA), and external factors, such as inflation and the SBI interest rate, are the variables used in this study. Design/methodology/approach - This study used the vector error correction model (VECM) as the research methodology. Findings - The results state that CAR and inflation variables have a positive and significant effect on FDR in the short term, but other variables are not significant. The financing-to-deposit ratio is negatively affected by ROA and BI interest rate variables in the long term, while in the short term it is positively affected by CAR and inflation (FDR) variables. Research limitations/ implications - In order to determine the liquidity policy of Islamic banking in the future, the authorities in Indonesia can benefit significantly from this research. Originality and value - This research can be used as a comparative reference for Islamic banking to maintain its liquidity. There are still not many studies that examine research on Islamic banking liquidity in Indonesia with these variables, so this journal can be a reference for further research. However, it is limited to 2015 to 2020 and only uses Islamic banking as the object of research. Keywo